Pengaruh Media Pop-Up Book Terhadap Hasil Belajar Siswa Materi Penggolongan Hewan Kelas III SDN 10 Simpang Teritip - Reindu Fitriana; Erika Fitri Wardani; Muhammad Iqbal Arrosyad (JBES (Journal Basic Education Skills), 2025)
This research is motivated by the fact that students find it difficult to distinguish the classification of animals based on thetype of food, causing low student learning outcomes. This study aims to determine the influence of pop up book media on the learning outcomes of students of animal group material based on the type of food ingrade III SDN10 Simpang TeritipThis type of research is quantitative, using a quasi-experimental design method with a nonequivalent control group design. The sample technique used is saturated sampling. The entire population, consisting of 16 students in the experimental class and 16 students inthecontrolclass,willbeusedasasample. The techniques of data collection were used in the form of summative test totaling five essay questions. The data analysis technique uses the Normality, he Homogeneity, and the Hypothesis tests using an independent sample t-test.Based on the results of descriptive analysis, it is known that the average score of the experimental class is higher than the control class (84.68>72.81). This is supported by the results of the hypothesis test using an independent sample t-test Significant 0.05 obtained ttable value = 0,00 < 0,05, so it can be concluded that there is an influence of the Guided Inquiry learning model material on changes in the form of objects on the learning outcomes of grade III students of SD Negeri 10 simpangteritip